Pengaruh Penerapan SIKEPO (Sistem Informasi Kinerja Pegawai Online) Terhadap Kinerja Pegawai Negeri Sipil di Badan Perencanaan Pembangunan Daerah Provinsi Bali - Ni Ketut Swandewi; Lilik Antarini; I Wayan Sudemen (Journal of Contemporary Public Administration, 2023)
The administrative system that was previously done manually greatly hampered employee performance in terms of time and cost so that the development of information technology can affect employee performance in playing a very important role in managing management information systems, such as the following: data entry, data management, and information data transmission. In adapting to the rapid development of technology, one example is the adaptation of technology used by the Bali Provincial Government, namely SIKePO (Online Employee Performance Information System). The SIKePO application is an application that records all daily activities of employees within the scope of the Bali Provincial Government. BAPPEDA Bali Province is one of the Bali Provincial government agencies that implements SIKePO with the hope that this system can be more effective and efficient in terms of time and cost to supervise the performance of civil servants. The problem of research on the application of SIKePO in BAPPEDA Bali Province is the influence of the application of SIKePO on the performance of civil servants, therefore, the purpose of this study was to determine how much influence the application of SIKEPO has on the performance of civil servants in the Regional Development Planning Agency of Bali Province. This research method is an associative research method with a quantitative approach. The data needed in this study are primary data and secondary data. Data collection techniques used through observation, questionnaires, and documentation. Data was obtained from a questionnaire distributed to all civil servants in BAPPEDA Bali Province containing a total of 32 respondents. The sampling method in this study used saturated samples. The population in this study is all civil servants in BAPPEDA Bali Province. Based on the results of this study, it shows that the correlation results between variables X and Y amounted to rxy = 0.534 which means that the variable application of SIKePO has a positive and significant effect on the Performance of Civil Servants, with a simple linear regression analysis of Y' = 5.64 + 0.67 X which means that there is a positive relationship (unidirectional between x and y) and the results of determination have an influence on the application of SIKePO stimultan has a contribution of 28.5% to the Performance of Civil Servants Civil, while the other 71.5% were contributions from other variables that were not studied in this study. It can be concluded that there is a significant relationship and the hypothesis proposed is proven correct.